Large-Scale Reduction in the Extent of Agriculture around Stopover Sites of Migratory Geese in European Russia between 1990 and 2015 - Grishchenko, Mikhail; Ydenberg, Ronald C.; Prins, Herbert H. T. (Diversity (Basel), 2023)
Stopover sites are vital to the state of the population of many migratory bird species. The greater white-fronted goose Anser albifrons is the most numerous Eurasian goose species, and migrates on a broad front over European Russia. Stopover and staging sites have specific habitat requirements. They are located near open water, have nearby (<5 km) foraging areas, must be open, and lie at least 500 m from the nearest woodland. Extensive agricultural land abandonment in European Russia since 1990 is leading to widespread land cover changes, and may be lowering the availability and perhaps the suitability of stopover sites for greater white-fronted geese. To measure the extent of land cover change, we compiled Landsat images of three areas in European Russia over which geese migrate. The images were taken May 1990, 2002 and 2014, and used to create a scene that covered completely each area in each of these years. We classified each pixel into one of six land cover classes (LCCs: urban, water, arable, grass, peat bog and forest), and tallied the number changing LCC between the successive maps. For ground truthing, we made field visits in June 2014 to 150 locations chosen randomly in advance, and among them, 64 identified as stopover sites recently used by geese. At each, we assessed vegetation composition and cover, successional stage and the duration (in years) since agriculture on the site had been abandoned. The extent of arable land that changed to another classification 1990–2014 was 56%, and was matched closely by the increase in the extent of the ‘grassland’ and ‘forest’ categories, as expected if agricultural abandonment allows vegetation succession to proceed. The magnitude of change around identified stopover sites was similar to that in the areas as a whole. The extent of land cover change in the northern part of European Russia is making migration by greater white-fronted geese more challenging, which is consistent with the documented southward shift in stopover site usage. This could lead to abandonment of the route across northern European Russia altogether, in favour of a longer migration around the expanding boreal forest, which is inhospitable for goose species.